Caveolin-1 expression in hyperproliferative skin disorders: A potential predictive marker of disease severity and progression - Shereen Farouk Gheida; Yomna Mazid El-Hamd Neinaa; Dareen Abd El-Aziz Mohammed (Wolters Kluwer Medknow Publications, 2018)
Background: Caveolin-1 (CAV-1) is a key structural and functional membrane protein that is thought to play a role in controlling cellular proliferation and differentiation. Objective: To study the immunohistochemical expression of caveolin-1 in psoriasis and the two common types of non-melanoma skin cancers (NMSCs); basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) in comparison to normal control skin and to correlate their expression with disease severity and progression. Patients and methods: This study included 90 patients and paraffin blocks (30 psoriasis, 30 BCC and 30 SCC) and 30 normal control skin specimens. Skin biopsy specimens were taken from all and examined for immunohistochemical expression of caveolin-1. Results: Significant reduction of caveolin-1 expression was detected in all studied patients groups in comparison to control group. Caveolin-1 expression in psoriasis showed significant downregulation with progression of Psoriasis Area and Severity Index (PASI) score. In addition, caveolin-1 expression was significantly decreased in aggressive types of BCC compared to non-aggressive types. Furthermore, poorly differentiated SCC showed significantly reduced caveolin-1 expression compared to moderately and well differentiated SCC. Conclusion: Caveolin-1 downregulation may increase the susceptibility to both benign and malignant hyperproliferative skin disorders. It could be useful as predictive biomarker of disease severity and progression. Keywords: Caveolin-1, Psoriasis, BCC, SCC